Antimicrobial Potential of Polyherbal Formulation Vidangadi Churna – A Review - Gupta, Dr Dinesh (International Journal of Pharmaceutical & Biological Archive, 2018)
Herbal medicines are the major remedy in traditional medical systems from thousands of years and made a great contribution in maintaining human health and in preventing many infectious diseases. Ayurvedic herbal preparations based on the medicinal plants are used in modern health care to prevent common microbial diseases but their antimicrobial potential was not evaluated in detail. Therefore antimicrobial potential of polyherbal formulation vidangadi churna mention in the text is taken for review. The authentic subject material has been reviewed from Ayurveda and modern medical literature. Different research and review article were searched in different journals to establish the antimicrobial potential of vidangadi churna